2016
DOI: 10.1111/asj.12635
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Meat quality traits as a function of cow maturity

Abstract: To investigate the physico-chemical and sensory properties of striploin muscles, 90 Hanwoo carcasses (QG 1 ) were randomly selected within six maturity levels (4 to 9 according to age in months). Results demonstrated that the protein contents at maturity levels 4 and 5 were significantly higher than 9. No significant difference in fat, moisture and collagen contents were found at different maturity levels (P > 0.05). The quantity of collagen type I and ratio of type I to III were observed at higher maturity le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 66 publications
(165 reference statements)
1
9
0
4
Order By: Relevance
“…Results of the present study also showed that collagen content was positively correlated with type I and type IIA fibers but negatively correlated with type IIB fiber. It is generally accepted that collagen type composition and concentration are strongly correlated with meat tenderness ( Cho et al , 2017 ). Thus, the lack of correlation between WBSF and FAP of type I fiber (r = −0.03) was unexpected.…”
Section: Resultsmentioning
confidence: 99%
“…Results of the present study also showed that collagen content was positively correlated with type I and type IIA fibers but negatively correlated with type IIB fiber. It is generally accepted that collagen type composition and concentration are strongly correlated with meat tenderness ( Cho et al , 2017 ). Thus, the lack of correlation between WBSF and FAP of type I fiber (r = −0.03) was unexpected.…”
Section: Resultsmentioning
confidence: 99%
“…Estes últimos autores relataram que apenas 8 % da variação das notas obtidas em painel sensorial poderia ser explicada pelo nível de GIM. Os resultados obtidos são contrários aos relatos do sabor e suculência como atributos altamente correlacionados com a quantidade de gordura presente na carne (Cho et al, 2017;Van Ba et al, 2016). Esta relação positiva entre GIM, sabor e suculência já foi estabelecida por painéis de consumidores comuns, embora estes tenham recebido amostras com variação bem mais elevada na marmorização (entre traço/ligeira à moderadamente abundante/abundante) sendo consumidores estadunidenses (Corbin et al, 2015;Emerson et al, 2013;Hunt et al, 2014;O'Quinn et al, 2012;Thompson, 2004), cujo sistema de classificação privilegia carne para consumo com elevada gordura intramuscular.…”
Section: Discussionunclassified
“…Este resultado diverge parcialmente, uma vez que não consegue diferenciar os animais jovens dos adultos e velhos, de relatos da diminuição de notas do painel sensorial de amostras de animais mais velhos quando comparados a animais jovens (Moon et al2006;Harris 1990 ;. Geralmente a carne de animais mais velhos é considerada menos macia em relação a animais jovens (Cho et al, 2017;Mojto et al, 2009;Xiong et al, 2007). Alguns autores consideram que os efeitos da maturidade são mais importantes para maciez do que fatores como marmorização, além de estarem correlacionados também com os parâmetros suculência, sabor e aceitação geral (Hilton et al 1998.…”
Section: Discussionunclassified
“…A idade ou maturidade em bovinos é importante, pois existem evidências de que a qualidade organoléptica da carne, principalmente a maciez, diminuem com o avanço da idade (SHORTOSE;HARRIS, 1990;CHO et al, 2017). Um dos fatores que explicam essa mudança é o colágeno, principal componente do tecido conjuntivo intramuscular junto a quantidades significativas de elastina e substância fundamental amorfa (JUNQUEIRA; CARNEIRO, 2013).…”
Section: Qualidade Da Carne Em Bovinos Adultosunclassified
“…A carne de animais fisiologicamente maduros é geralmente considerada menos macia em relação a carne de animais jovens (XIONG et al, 2007;MOJTO et al, 2009;CHO et al, 2017), sendo isso associado ao estado de solubilidade do colágeno, ou seja, do grau e tipo de ligações cruzadas presentes no tecido conjuntivo (SHORTOSE; HARRIS, 1990). Isso ocorre durante o envelhecimento, no qual, formam-se ligações cruzadas entre as moléculas de colágeno, fazendo que com essa proteína se torne termo-estável (NISHIMURA, 2010; PURSLOW, 2012).…”
Section: Qualidade Da Carne Em Bovinos Adultosunclassified